RIDESOURCING IN MANUFACTURING SITES: A FRAMEWORK AND CASE STUDY - Park, Kangah; Lim, Jungeun; Hwang, Woohyun; Park, Junhyun; Song, Minseok; Kim, Byung-In; Park, Jung Goo; Choi, Doo Jin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
With the recent innovations in transportation, ridesourcing services have been proliferating in many countries. There are increasing attempts to apply ridesourcing in the corporate context. Manufacturing companies now install the Industrial Internet of Things (IIOT) sensors to vehicles to obtain real-time data on the movement of goods and materials. Despite the massive amount of data accumulated, little attention has been paid to exploiting the data for vehicle fleet management (FM). This paper proposes an analytical framework to solve two FM problems: how to group organizational units for vehicle sharing and where to deploy the groups. The framework is then validated with a case study of a Korean shipbuilder. The results indicate that grouping departments with similar spatial patterns can reduce the current fleet.